The integration of ecosystem services into computable general equilibrium modeling: State of the art and ways forward - Alexandra Marques; Onil Banerjee; Lukas Eggert; Paula A. Harrison; Tobias Heimann; Justin Johnson; Alessandra La Notte; Alexander Popp; Martin Quaas; Catharina J.E. Schulp; Willem-Jan van Zeist; Patrick von Jeetze; et al. (Global Environmental Change, 2026)

A Global Assessment of Plant and Animal Community Responses to Forest Management Over Time - Hanneke van 't Veen; Koen Kuipers; Aafke Schipper; Alexandra Marques; Mart‐Jan Schelhaas; Rob Alkemade (Global Change Biology, 2025)
Transitions to forest management that mitigate negative effects of forest use on biodiversity are required to bend the curve of biodiversity loss. To facilitate such transitions, it is vital to understand the effects of different forest management practices on biodiversity. In this study, we analyzed observation data of 182 studies (312,453 abundance values) from three global biodiversity databases to estimate the effects of seven types of forest management on plant and animal (i.e., insects and vertebrates) biodiversity over time, and on threatened animals. We captured biodiversity in four distinct metrics (i.e., quantifiable measures of community composition): (i) intactness, (ii) relative species richness, (iii) compositional similarity, and (iv) relative total abundance, all calculated as the difference in biodiversity between managed and undisturbed forests. Overall, we find larger effects of forest management on intactness and similarity compared to richness and abundance. This suggests that forest management leads to a loss of species that specifically occur in undisturbed forests but that this decline is partially offset by an influx of species from other areas. We find that extensive forest management, such as selective cutting and agroforestry, supports higher levels of overall and threatened biodiversity than intensive management, such as forest and perennial tree crop plantations. We also find significant increases in animal community intactness and similarity in agroforests and forest plantations over 40 and 80 years since establishment, respectively, but do not find this for relative species richness and total abundance. This indicates that animal communities in these management systems become increasingly similar to those of undisturbed forests. Overall, our results highlight the potential of selective cutting and agroforests to mitigate biodiversity loss compared to more intensive systems, as well as the potential of longer rotation periods in forest plantations to increase habitat availability for species specifically adapted to undisturbed forests.

Integrating high-resolution remote sensing and empirical wildlife detection data for climate-resilient corridors across tropical elevational gradients - Ian M. McCullough; Christopher Beirne; Carolina Soto-Navarro; Amy Eppert; Eleanor Flatt; Yvonne J.M. Kemp; Péter K. Molnár; Michael S. Mooring; Yana Nikolova; Erik R. Olson; Carolina Pinto; Junior Porras; et al. (Biological Conservation, 2024)

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Assessing ambitious nature conservation strategies in a below 2-degree and food-secure world - Marcel T.J. Kok; Johan R. Meijer; Willem-Jan van Zeist; Jelle P. Hilbers; Marco Immovilli; Jan H. Janse; Elke Stehfest; Michel Bakkenes; Andrzej Tabeau; Aafke M. Schipper; Rob Alkemade (Biological Conservation, 2023)

Prediction of particulate fouling in full-scale reverse osmosis plants using the modified fouling index – ultrafiltration (MFI-UF) method - Mohanad Abunada; Nirajan Dhakal; Raffay Gulrez; Pamela Ajok; Yuke Li; Almotasembellah Abushaban; Herman Smit; David Moed; Noreddine Ghaffour; Jan C. Schippers; Maria D. Kennedy (Desalination, 2023)

Are floating treatment wetlands more suitable for retrofitting highway runoff basins than vertical-flow treatment wetlands? - Hannah Wirtz; Jan P. Ruppelt; Jos H.M. Schippers; Andrea E. Neinhuis; Laura Luetjens; Joost T. van Dongen; Johannes Pinnekamp; Katharina Tondera (Ecological Engineering, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Projecting terrestrial biodiversity intactness with GLOBIO 4 - Aafke M. Schipper; Jelle P. Hilbers; Johan R. Meijer; Laura H. Antão; Ana Benítez‐López; Melinda M. J. de Jonge; Luuk H. Leemans; Eddy Scheper; Rob Alkemade; Jonathan C. Doelman; Sido Mylius; Elke Stehfest; et al. (Global Change Biology, 2020)
Scenario‐based biodiversity modelling is a powerful approach to evaluate how possible future socio‐economic developments may affect biodiversity. Here, we evaluated the changes in terrestrial biodiversity intactness, expressed by the mean species abundance (MSA) metric, resulting from three of the shared socio‐economic pathways (SSPs) combined with different levels of climate change (according to representative concentration pathways [RCPs]): a future oriented towards sustainability (SSP1xRCP2.6), a future determined by a politically divided world (SSP3xRCP6.0) and a future with continued global dependency on fossil fuels (SSP5xRCP8.5). To this end, we first updated the GLOBIO model, which now runs at a spatial resolution of 10 arc‐seconds (~300 m), contains new modules for downscaling land use and for quantifying impacts of hunting in the tropics, and updated modules to quantify impacts of climate change, land use, habitat fragmentation and nitrogen pollution. We then used the updated model to project terrestrial biodiversity intactness from 2015 to 2050 as a function of land use and climate changes corresponding with the selected scenarios. We estimated a global area‐weighted mean MSA of 0.56 for 2015. Biodiversity intactness declined in all three scenarios, yet the decline was smaller in the sustainability scenario (−0.02) than the regional rivalry and fossil‐fuelled development scenarios (−0.06 and −0.05 respectively). We further found considerable variation in projected biodiversity change among different world regions, with large future losses particularly for sub‐Saharan Africa. In some scenario‐region combinations, we projected future biodiversity recovery due to reduced demands for agricultural land, yet this recovery was counteracted by increased impacts of other pressures (notably climate change and road disturbance). Effective measures to halt or reverse the decline of terrestrial biodiversity should not only reduce land demand (e.g. by increasing agricultural productivity and dietary changes) but also focus on reducing or mitigating the impacts of other pressures.

Seismic assessment of a lab-tested two-storey unreinforced masonry Dutch terraced house - Rita Esposito; Francesco Messali; Geert J. P. Ravenshorst; H. Roel Schipper; Jan G. Rots (Bulletin of Earthquake Engineering, 2019)

Observations and Modelling of Shoreface Nourishment Behaviour - Bastiaan Huisman; Dirk-Jan Walstra; Max Radermacher; Matthieu de Schipper; B. Gerben Ruessink (Journal of Marine Science and Engineering, 2019)
Shoreface nourishments are commonly applied for coastal maintenance, but their behaviour is not well understood. Bathymetric data of 19 shoreface nourishments located at alongshore uniform sections of the Dutch coast were therefore analyzed and used to validate an efficient method for predicting the erosion of shoreface nourishments. Data shows that considerable cross-shore profile change takes place at a shoreface nourishment, while an impact at the adjacent coast is hard to distinguish. The considered shoreface nourishments provide a long-term (3 to ∼30 years) cross-shore supply of sediment to the beach, but with small impact on the local shoreline shape. An efficient modelling approach is presented using a lookup table filled with computed initial erosion–sedimentation rates for a range of potential environmental conditions at a single post-construction bathymetry. Cross-shore transport contributed the majority of the losses from the initial nourishment region. This transport was driven partly by water-level setup driven currents (e.g., rip currents) and increased velocity asymmetry of the waves due to the geometrical change at the shoreface nourishment. Most erosion of the nourishment takes place during energetic wave conditions ( H m 0 ≥ 3 m) as milder waves are propagated over the nourishment without breaking. A data-model comparison shows that this approach can be used to accurately assess the erosion rates of shoreface nourishments in the first years after construction.

Disentangling and ranking the influences of multiple environmental factors on plant and soil-dwelling arthropod assemblages in a river Rhine floodplain area - Aafke M. Schipper; A. Jan Hendriks; Ad M. J. Ragas; Rob S. E. W. Leuven (Hydrobiologia, 2014)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Modelling the impact of toxic and disturbance stress on white-tailed eagle (Haliaeetus albicilla) populations - John C. Korsman; Aafke M. Schipper; H. J. Rob Lenders; Ruud P. B. Foppen; A. Jan Hendriks (Ecotoxicology, 2012)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Maximum Photosynthetic Yield of Green Microalgae in Photobioreactors - Jan-Willem F. Zijffers; Klaske J. Schippers; Ke Zheng; Marcel Janssen; Johannes Tramper; René H. Wijffels (Marine Biotechnology, 2010)

Potential role of ticks as vectors of bluetongue virus - Chantal Bouwknegt; Piet A. van Rijn; Jacqueline J. M. Schipper; Dennis Hölzel; Jan Boonstra; Ard M. Nijhof; Eugène M. A. van Rooij; Frans Jongejan (Experimental and Applied Acarology, 2010)

Using datasets of different taxonomic detail to assess the influence of floodplain characteristics on terrestrial arthropod assemblages - Aafke M. Schipper; Kim Lotterman; Marten Geertsma; Rob S. E. W. Leuven; A. Jan Hendriks (Biodiversity and Conservation, 2010)

The Future of Tropical Species on a Warmer Planet - S. JOSEPH WRIGHT; HELENE C. MULLER‐LANDAU; JAN SCHIPPER (Conservation Biology, 2009)
Modern global temperature and land cover and projected future temperatures suggest that tropical forest species will be particularly sensitive to global warming. Given a moderate greenhouse gas emissions scenario, fully 75% of the tropical forests present in 2000 will experience mean annual temperatures in 2100 that are greater than the highest mean annual temperature that supports closed‐canopy forest today. Temperature‐sensitive species might extend their ranges to cool refuges, defined here as areas where temperatures projected for 2100 match 1960s temperatures in the modern range. Distances to such cool refuges are greatest for equatorial species and are particularly large for key tropical forest areas including the Amazon and Congo River Basins, West Africa, and the upper elevations of many tropical mountains. In sum, tropical species are likely to be particularly sensitive to global warming because they are adapted to limited geographic and seasonal variation in temperature, already lived at or near the highest temperatures on Earth before global warming began, and are often isolated from cool refuges. To illustrate these three points, we examined the distributions and habitat associations of all extant mammal species. The distance to the nearest cool refuge exceeded 1000 km for more than 20% of the tropical and less than 4% of the extratropical species with small ranges. The biological impact of global warming is likely to be as severe in the tropics as at temperate and boreal latitudes.

Cognitive and psychomotor effects in males after smoking a combination of tobacco and cannabis containing up to 69 mg delta-9-tetrahydrocannabinol (THC) - Claudine C. Hunault; Tjeert T. Mensinga; Koen B. E. Böcker; C. Maarten A. Schipper; Maaike Kruidenier; Marianne E. C. Leenders; Irma de Vries; Jan Meulenbelt (Psychopharmacology, 2009)

The Effect of Atmospheric Carbon Dioxide Elevation on Plant Growth in Freshwater Ecosystems - Peter Schippers; Wolf M. Mooij; Jan E. Vermaat; Jeroen de Klein (Ecosystems, 2004)